Positional cloning of the gene responsible for dent's disease - Fisher, S; Simon E. Fisher (1995)
﻿ The hypervariable locus DXS255 in human Xp11.22 has a heterozygosity exceeding 90% and has therefore facilitated the localization of several disease genes which map to the proximal short arm of the X chromosome, including the immune deficiency Wiskott-Aldrich syndrome and the eye disorders retinitis pigmentosa, congenital stationary night blindness and Aland Island eye disease. In addition, a microdeletion involving DXS255 has been identified in patients suffering from Dent's disease, a familial X-linked renal tubular disorder which is characterized by low molecular weight proteinuria, hypercalciuria, nephrocalcinosis, nephrolithiasis (kidney stones) and eventual renal failure. Two YAC contigs were constructed in Xp11.23-p11.22 in order to aid transcript mapping; the first centred on the DXS255 locus, the second mapping distal to the first and linking the genes GATA, TFE3 and SYP to the OATL1 cluster. Eleven novel markers were generated, one of which contains an exon from a novel calcium channel gene. Four putative CpG islands were detected in the region. Analysis of the microdeletion associated with Dent's disease using markers from the DXS255 contig demonstrated that it is confined to a 370kb interval. A YAC overlapping this deletion was hybridized to a kidney-specific cDNA library to isolate coding sequences that might be implicated in the disease aetiology. The clones thus identified detect a 9.5kb transcript which is expressed predominantly in kidney, and originate from a novel gene (CLCN5) falling within the deleted region. Sequence analysis indicates that the 746 residue protein encoded by this gene is a new member of the C1C family of voltage-gated chloride channels. The coding region of CLCN5 is organized into twelve exons, spanning 25-30kb of genomic DNA. Using the information presented in this thesis, other studies have identified deletions and point mutations which disrupt CLCN5 activity in further patients affected with X-linked hypercalciuric nephrolithiasis, confirming the role of this locus in renal tubular dysfunction.